A New Trend in Pneumatic Drilling Machine - Vasumathi, G. (International Journal of Psychosocial Rehabilitation, 2018)
Our project aim is designing a voice operating pneumatic clamping device in drilling machine. In a normal drilling machine the machine vice is used to clamp the work piece. But it’s some difficult to hold the irregular work piece in certain position. Because of our two hands are used to position the work piece in the drilling machine. And then the external source is needed to fitting the job (or) work piece. For this purpose we provided voice operating pneumatic clamping device in drilling machine. Now a day the normal drilling machine is used in own small companies.